Training the Next Generation: Developing Health Education Skills in Undergraduate Public Health Students at a Historically Black College and University - Mincey, Krista; Gross, Tyra (Frontiers in Public Health, 2017)
With the looming workforce crisis, undergraduate public health students could be an important link in filling this demand. As public health continues to face challenges in the future, it is important that the future workforce is not only diverse but also trained in a manner that exposes them to real world experiences that give them an opportunity to apply coursework to solve problems. This article outlines how a health program planning course was taught at a HBCU using assignments that promote active learning. Students were assessed on their ability to plan and implement a health activity based on a developed metric. Student and instructor reflections were collected from final assessments of the health programs by both groups. All elements of the course are discussed from course design, structure, assignments, and outcomes along with student and instructor reflections and lessons learned. Results suggest that including assignments focused on active learning are beneficial to helping students learn course material. As public health continues to change, more work needs to focus on teaching pedagogies that better prepare students to address future public health issues.